REVIEW: PEMANFAATAN BIOCHAR UNTUK MENINGKATKAN KUALITAS TANAH DAN PRODUKTIVITAS TEBU - Putra, Rivandi Pranandita; Kusuma Dewi, Vita Ayu; Ridla Ranomahera, Muhammad Rasyid; Arini, Nindya; Haris, Amnan (Fakultas Pertanian, Universitas Janabadra, 2024)
Biochar is a solid material resulting from biomass carbonization which is generally made through a pyrolysis process, namely the thermal decomposition of biomass under anoxic conditions. Various previous studies have shown that biochar can have multiple positive impacts on soil quality and sugar cane productivity. Biochar can increase plant growth and development through several mechanisms, namely increasing nutrient use efficiency, increasing the amount and availability of nutrients, reducing nutrient leaching and nutrient loss through evaporation, promoting plant growth hormones, and reducing salinity stress. What is interesting is that improving the physical, chemical, and biological quality of soil by biochar allows for reducing the dose of inorganic fertilizer that must be applied to sugarcane. Biochar can be made from various local materials, including unused sugar cane biomass (dry leaves, stem shoots, litter, etc.) and sugar factory waste. Biochar can be applied together with various other materials, such as organic, biological, and inorganic fertilizers to create a more positive synergistic effect on soil quality and plant growth and development. The results of the strength-weakness-opportunity-threat (SWOT) analysis show that the advantages of using biochar based on sugar cane biomass and sugar factory waste, are 1) it is cheap and easy to obtain, 2) contributes to reducing the volume of waste, 3) is one of the carbon sequestration methods effective, and 4) can improve the physical, chemical and biological quality of the soil. The disadvantages are 1) it requires high costs for collection, storage, and transportation to the field and 2) there is high variability in the content of biochar-making materials and soil conditions. Opportunities include the need for farmers to reduce production costs, including fertilizer costs, and increasing awareness of various parties regarding environmental issues, for example about the importance of carbon sequestration and environmentally friendly agriculture. Meanwhile, the threat is that biochar production on a large scale still seems difficult and some farmers still lack confidence or trust in biochar products.. Key-words: biochar, sugarcane biomass, sugar mill waste